Topological algebra via inner product - Azram, Mohammad (2014)
This paper is devoted to establish a probability measure on a unital commutative separable Fréchet Q lmc* - algebra. Consequently a new technique to define an inner product on a unital commutative semi simple separable Fréchet Q lmc* -algebra. We have shown that the resulting inner product space is a topological algebra. At the end we have established some properties of the introduced inner product.